2019
DOI: 10.3390/agronomy9030157
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Development of ‘Mini Chal’ Tomato Plug Seedlings Grown under Various Wavelengths Using Light Emitting Diodes

Abstract: This study aimed to determine the effects of various light qualities (green (G), ultraviolet-A (UV-A), and far-red (Fr)) on the growth and development of tomato plug seedlings. The ‘Mini Chal’ tomato (Solanum lycopersicum L.) seedlings were used as the plant material to which various light qualities were supplied. Fluorescent lamp (FL), combined FL and diniconazole (Dini), and R3B7 (red (R):blue (B) = 30:70) were used as the control. The different light treatments for this experiment were as follows: two G lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 84 publications
3
25
0
Order By: Relevance
“…Importantly, the DQI was greater in seedlings grown with the +10 • C DIF than those in the other two treatments, implying the ability of the +10 • C DIF to yield high-quality plug seedlings. The biomass, stem diameter, and DQI are important parameters used to evaluate the quality of seedlings [34][35][36]. These results were in accordance with previous studies in tomato [19,37] and sweet pepper [38].…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the DQI was greater in seedlings grown with the +10 • C DIF than those in the other two treatments, implying the ability of the +10 • C DIF to yield high-quality plug seedlings. The biomass, stem diameter, and DQI are important parameters used to evaluate the quality of seedlings [34][35][36]. These results were in accordance with previous studies in tomato [19,37] and sweet pepper [38].…”
Section: Discussionsupporting
confidence: 91%
“…In UV-A treatments, the stem diameter was not significantly different by UV-A intensity. In our previous study, stem diameter of tomato seedling was increased under Fr light treatment; however, there are non-significant differences in R/Fr ratios [22]. It seems that there are species differences in tomato and cucumber plants.…”
Section: Resultsmentioning
confidence: 67%
“…Plants 2020, 9, x FOR PEER REVIEW 7 of 13 treatment; however, there are non-significant differences in R/Fr ratios [22]. It seems that there are species differences in tomato and cucumber plants.…”
Section: Resultsmentioning
confidence: 99%
“…moreover, while HPS technology emits a large range of the SL spectrum between the yellow-orange wavelength, with LEDs, it is possible to optimize the spectral quality for various plants and different physiological processes [9]. Consequently, recent studies have shown that for tomato plants, the best LED SL spectrum for increasing tomato production is red + blue (RB) [10], with about 90-95% of the total radiation on the red (R) wavelength and 5-10% on the blue wavelength (B) [11][12][13]. moreover, when giving a small percentage of green (G) light on the RB background, the SL penetration on plant canopy increases [14].…”
Section: Introductionmentioning
confidence: 99%